1996
DOI: 10.1364/ao.35.004112
|View full text |Cite
|
Sign up to set email alerts
|

Laser bandwidth effects in quantitative cavity ring-down spectroscopy

Abstract: We have investigated the effects of laser bandwidth on quantitative cavity ring-down spectroscopy using the (r)R transitions of the b(ν = 0)?X(ν = 0) band of molecular oxygen. It is found that failure to account properly for the laser bandwidth leads to systematic errors in the number densities determined from measured ring-down signals. When the frequency-integrated expression for the ring-down signal is fitted and measured laser line shapes are used, excellent agreement between measured and predicted number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 10 publications
1
80
0
Order By: Relevance
“…The effect of laser bandwidth is unimportant for aerosols, since particle extinction is a broadband feature (Hodges et al 1996). The effects of laser phase noise are mainly important for continuous wave (cw)-CRDS (Morville et al 2002), due to the tight overlap of bandwidth and cavity mode width.…”
Section: The Crdsmentioning
confidence: 99%
“…The effect of laser bandwidth is unimportant for aerosols, since particle extinction is a broadband feature (Hodges et al 1996). The effects of laser phase noise are mainly important for continuous wave (cw)-CRDS (Morville et al 2002), due to the tight overlap of bandwidth and cavity mode width.…”
Section: The Crdsmentioning
confidence: 99%
“…This phenomenon has been discussed extensively in the literature. [11][12][13] Research to extend the present analysis to cover this case is in progress in our laboratory. An important ingredient is the analysis of all decay transients obtained at various frequency settings over the line profile in one procedure; hence an ensemble fit is performed over all data to yield absolute absorption cross sections of narrow molecular absorption features.…”
Section: Discussionmentioning
confidence: 98%
“…In certain experimental conditions the frequency spectrum of a CRD cavity is white, a necessary condition for retrieving absolute absorption cross sections with pulsed CRD spectroscopy. 13 For a well-aligned setup a reliable estimate of the absolute number of photons in the cavity can be given at any time during the decay. With the numbers of photons in the cavity known it is possible to investigate quantitatively intensity-dependent absorptions with the CRD technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Zalicki and Zare [24] have shown that for small absorptions the measured integrated absorption deviates only slightly from the true integrated absorption, again as in a traditional absorption measurement. Several authors have investigated the bandwidth effect in CRDS [18,[24][25][26][27].…”
Section: A More Refined Picturementioning
confidence: 99%